Factors affecting light energy transfer in some samarium complexes - Esam Bakier; M. S. A. Abdel-Mottaleb (International Journal of Photoenergy)
The photophysical properties of samarium ion in presence of 7-Acetoxy Coumarin 3-Carboxylic acid (ACC) or 1-(4-methoxyphenyl) 3-(4-t-butyl phenyl) 1,3-propandione (MBPK), which act as antenna of near-UV radiation, are studied in different homogeneous, and heterogeneous media as well as in rigid polymethylmethacrylate matrix (PMMA). High quantum yield value of the sensitized emission of (Sm3+ -(ACC)) and (Sm3+ -(MBPK)) in N,N-dimethylformamide and PMMA matrix are obtained pointing to an efficient ligandto- metal energy transfer. Moreover, luminescence mappings for pattern recognition analysis that could be profitably exploited as a useful identification method in clinical chemistry and biochemistry have been obtained from which the nature of the solvent and/or the ligand is clearly identified by inspection of the corresponding excitation/emission matrix maps.